Adaptive Capacity to Climate Variability in Three Rural Communities at Sierra de San Pedro Martir - González Ornelas, Itzel; Muñoz Meléndez, Gabriela (Frontera Norte, 2021)
Climate change adaptation has multiple definitions, to have a reference conceptual framework we understand it as the reduction of vulnerability to climate variability. This paper’s objective was to assess the adaptive capacity and response to climate variability in three rural communities at Sierra de San Pedro Martir National Park. We applied discourse analysis and non-participatory observation. As for data collecting, we carried out structured interviews during community workshops and semi-structured ones to external stakeholders. Results show that communities recognized droughts as the most important climate phenomenon, given that it impacts their economic activities and daily life alike. But inhabitants did not associate water availability to environmental services provided by the National Park. Our main contribution was modifying the methodological tool. Conclusions indicate that adaptive responses are associated with social characteristics of the local population and their strategies diversity. The public institutions’ role in rural adaptation was not addressed in-depth.